Tauriana: An ancient settlement on the Via Axia Road, in Nov Dojran (Archaeologia Adriatica, 2026)
The ancient settlement of Tauriana, located near present-day Nov Dojran in Macedonia, constitutes a significant archaeological and historical site, identified as the final station on the Via Axia, a Roman-period road documented on the well-known Tabula Peutingeriana. It ran from Thessaloniki towards the northern frontier of the Roman Empire, following the valley of the River Axios (modern-day Vardar), having served as a vital corridor of movement as early as the Hellenistic and early Roman periods. The valley functioned as an important ancient communication and transportation route, facilitating trade, military campaigns and cultural exchange between the southern and northern parts of the empire. Although written sources specifically referring to Tauriana are scarce, archaeological excavations conducted in the area of Nov Dojran have revealed significant remains indicating the presence of a developed settlement with urban characteristics during the Roman Imperial period. Throughout contemporary Nov Dojran, remains of architectural structures, necropolises and a large number of movable finds such as pottery, coins, and jewellery have been uncovered. These artefacts are dated to both the early and late Roman imperial periods, confirming the site’s longterm occupation and importance. Such archaeological evidence suggests that Tauriana was not merely a transit station along the Roman road network, but rather a local urban centre with economic and cultural relevance. Although Tauriana has not been thoroughly studied (unlike other ancient cities and settlements in Macedonia) and remains somewhat overshadowed by larger urban centres, it nonetheless serves as a key indicator for understanding the regional role of Dojran in antiquity, particularly within the broader context of the integration of this territory into the infrastructure and administrative system of the Roman Empire.
Keywords: Tabula Peutingeriana; Antiquity; Roman period; Tauriana; Via Axia; ancient road networks; archaeological research; Nov Dojran